MO200COVID-19 PANDEMIC INCREASED ADVANCE CARE PLANNING DEMAND. (29th May 2021) - Toccafondi, Alessandro; Simone, Giuseppina; Lombardi, Marco; Dattolo, Pietro Claudio
Abstract: Background and Aims: Advance care planning (ACP) enables competent patients to define goals and preferences for future treatments and care, to discuss these goals and preferences with relatives, and if appropriate to record these preferences. After many years of political and social debates, in December 2017 the first advance directive and care planning legislation was approved in Italy. Nevertheless, citizens' awareness of these issues is scarce as well as the integration of the advance care planning process into clinical routine. The latest data reported to the Italian Parliament by the Ministry of Health indicated that advance directives have been completed by 62030 people, approximately 1.1% of Italian adult population. However, during the last months, the COVID-19 pandemic solicited taking steps towards promoting an advance care planning culture. Indeed, the need of proposing ACP to patients have been recently stressed both by medical associations and national and local institutional documents. Method: Since November 2020, our nephrology unit adopted a protocol approved by Ethical committee by Physician Order of Florence, aimed to conduct ACP interventions with dialysis patients. Firstly, all patients were informed about the possibility to taking part in one or more advance care planning conversations with their nephrologist. Secondly, a semi-structured guide to the conversation was created in order to support physicians in conducting the ACP intervention. Finally, patients along with nephrologist and their relatives, could documented their preferences for future treatments and care. Results: From November to March only one patient asked to receive an ACP intervention. However, since COVID-19 spread in Italy last March, the number of patients who demanded ACP raised up. In the period from April to July, 15 out of 110 hemodialysis patients treated in our center asked for an ACP intervention and filled-in an advance directive. Specifically, no patients required an immediate discontinuation of dialysis, nevertheless 80% of them stated that would not like to continue with dialysis in case he/she was no longer able to self-determine (e.g. permanent loss of capacity to communicate with others). All patients except one have appointed a personal representative (usually their partner). In the eventuality of cardiac arrest, 60% of patients asked for cardiopulmonary resuscitation. Finally, all patients expressed the wish to spend the last days of life at home. Conclusion: The COVID-19 pandemic raised up the number of dialysis patients who required to taking part in a advance care planning intervention. In this sense, the pandemic can be an opportunity for consolidate advance care planning in Italy as well as in other countries, where these interventions are not well known by people and not yet regularly offered in the clinical routine. Using a semi-structured interview for the ACP interview can help the nephrologist to discuss future care and end-of-life topics with their patients.